The game as a means of development of social competence of pupils - Gorbunova A. Y. (Pedagogical experience: theory, methodology, practice, 2016)
This article is devoted to the study of the concept of "competence", as well as the study of methods of teaching physical education, contributing to the development of communication skills of students.
Keywords: игра; физкультура; социальная компетенция; game; social competence; exercise